Resveratrol regulates insulin resistance to improve the glycolytic pathway by activating SIRT2 in PCOS granulosa cells - Liang, Aihong; Zhang, Wenmao; Wang, Qian; Huang, Lan'e; Zhang, Jiaming; Ma, Duo; Liu, Ke; Li, Shiyu; Chen, Xi; Li, Shan; Lei, Xiaocan (Frontiers in Nutrition, 2023)
Insulin resistance (IR) has a closely relationship with the main clinical manifestations of PCOS patients, hence the research and development of new drugs to treat PCOS by improving IR is a desiderate task at present. Resveratrol (RES) possesses a variety of beneficial pharmacological functions, such as antioxidation, anti-inflammatory, regulating glucose and lipid metabolism and so on. However, whether RES could improve IR and the underlying mechanisms remained unclear in PCOS. In the present study, SD rats received a high fat diet and letrozole for 30 days to establish the PCOS model, and then intervened with RES for 30 days. Results demonstrated that RES played a protective role on the IR in PCOS rats, which significantly decreased the levels of blood glucose and serum insulin, up-regulated the expression of IGF1R and down-regulated the expression of IGF1. In vitro, KGN cells were treated with insulin, RES and AGK2 respectively. We found that high dose of insulin (4 μg/mL) significantly inhibited KGN cells viability, decreased the level of lactic acid and increased the level of pyruvate. While RES (25 μM) attenuated the growth-inhibitory effect, as well increased the level of lactic acid and decreased the level of pyruvate after high levels of insulin treatment. Simultaneously, RES up-regulated the expression level of the crucial rate limiting enzymes relating to glycolytic pathway like LDHA, HK2 and PKM2. Furthermore, AGK2 remarkablely inhibited the expression level of SIRT2, which was similar to the same negative effects processed by insulin. Meanwhile, RES overtly repaired the glycolysis process by reversing the levels of lactic acid and pyruvate, together with up-regulating the expression level of LDHA, HK2 and PKM2 after AGK2 treatment. These results indicated that RES could effectively improve the insulin resistance and restore the glycolysis pathway by regulating SIRT2, which may contribute to attenuate the ovarian damages of PCOS rats and provide a potential treatment for PCOS patients.